2020
DOI: 10.1177/2158244020983299
|View full text |Cite
|
Sign up to set email alerts
|

Toward Reducing Adolescents’ Bottled Water Purchasing: From Policy Awareness to Policy-Congruent Behavior

Abstract: Policy awareness increases the likelihood of policy-congruent behavior. Yet individuals may differ in the extent to which they notice certain policies; thus, psychological factors that explain behavior can have a differing effect on policy-congruent behavior of individuals. We investigated to what extent the relationship between normative, habitual, intentional, and situational factors that explain bottled water purchasing behavior vary regarding individuals’ awareness of policy targeted at reducing bottled wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
2
10
0
1
Order By: Relevance
“…These findings are consistent with past studies, which reported that advertising could shape consumer perceptions of BW quality, including cleanliness, taste, nutritional values, health benefits and safety (e.g., Klein and Huang 2008;Ward et al 2009;Jovarauskaitė et al 2020). This type of cognitive beliefs could then influence consumer attitude and purchase intention toward BW products.…”
Section: Consumer Beliefs and Theory Of Reason Actionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with past studies, which reported that advertising could shape consumer perceptions of BW quality, including cleanliness, taste, nutritional values, health benefits and safety (e.g., Klein and Huang 2008;Ward et al 2009;Jovarauskaitė et al 2020). This type of cognitive beliefs could then influence consumer attitude and purchase intention toward BW products.…”
Section: Consumer Beliefs and Theory Of Reason Actionsupporting
confidence: 90%
“…As aforementioned, misleading information permeated through advertising messages about BW as a high-quality and safe choice preferred by consumers has helped create positive cognitive beliefs about BW consumption (Klein and Huang 2008;Ward et al 2009;Jovarauskaitė et al 2020). Advertising campaigns have also been found to lead a majority of consumers to believe BW's superiority over tap water (e.g., Hu et al 2011).…”
Section: Consumer Beliefs and Theory Of Reason Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Everyday app-based reminders to pour some tap water were used as prompts. We also expected that prompts will assist in breaking the habit of bottled water use, which, as found by Jovarauskaitė and colleagues [26], is an important predictor of behavior in adolescence. In previous research, when testing the habit discontinuity theory [27], prompts were proven to be an effective strategy for the change of habitual behavior [28].…”
Section: The Current Studymentioning
confidence: 84%
“…Age is considered as an important factor that influences people's perception and implementation of policies on waste separation [58][59][60][61]. Although previous research has demonstrated that children take a strong stance toward protecting the natural environment, it was found that adolescents engage less in pro-environmental behaviors [58].…”
Section: The Present Studiesmentioning
confidence: 99%